Drones for parcel and passenger transportation: A literature review. (March 2020) - Kellermann, Robin; Biehle, Tobias; Fischer, Liliann
Abstract: Delivery drones and 'air taxis' are currently among the most intensely discussed emerging technologies, likely to expand mobility into the 'third dimension' of low-level airspace. This paper presents a systematic literature review of 111 interdisciplinary publications (2013 - 03/2019). The review systematizes the current socio-technical debate on civil drones for transportation purposes allowing for a (critical) interim assessment. To guide the review process four dimensions of analysis were defined. A total of 2581 relevant quotations were subdivided into anticipated barriers (426), potential problems (1037), proposed solutions (737) and expected benefits (381). We found that the debate is characterized by predominantly technical and regulatory problems and barriers which are considered to prevent or impede the use of drones for parcel and passengers transportation. At the same time, definite economic expectations are juxtaposed with quite complex and differentiated concerns regarding societal and environmental impacts. Scrutinizing the most prevalent transportation-related promises of traffic reduction, travel time saving and environmental relief we found that there is a strong need to provide scientific evidence for the promises linked to the use of drones for transportation. We conclude that the debate on drones for transportation needs further qualification, emphasizing societal benefits and public involvement more strongly. Highlights: Articles discussing the subject of drones for parcel and passenger transportation have seen drastic increase since 2013 Debates on drones are strongly dominated by technical and regulatory issues Future development of drone technologies will be increasingly dependent on public acceptance Transport-related promises of delivery drones and 'air taxis' (traffic and travel time reduction, environmental relief) often appear oversimplified or are yet lacking a scientific validation There's a need to further qualify the benefits of parcel and passenger drones in support of a participatory debate on a societal scale